Biodegradable Wet Wipes from Palm Fiber Combined with Extract from Palm Leaves as Antibacterial Agent - Fadilah Fadilah; Divanda Sekar Rahayu Ningtyas; Audrey Vista Candra Dewi; Anita Budi Krisnawati; Reyza Fachrezy Putra (Equilibrium Journal of Chemical Engineering, 2023)
Abstract. Palm fibers waste as the side-product from palm oil process can potentially be used as raw material for making green (biodegradable) wet wipes. It is proven that palm fiber contains cellulose by 87,3% of the results of cellulose analysis. Palm leaves are considered sufficiently as antibacterical agent due to containing the high-concentration polyphenol. This research aims to comprehend to process making wet wipes from palm fiber, then be combined with palm leaves extract as antibacterical agent. Pulp, made from palm fiber, is separated to two parts, with-bleaching sample and unbleaching sample.  bleaching sample needs three times bleaching with 120 mL H2O2 with a constan temperature of 70oC. The results of tissues with bleaching are stronger because the lignin content is reduced so that it is easy to bond with each other. The best bleaching tissue samples were obtained from the 7th experiment with a composition of 60 g palm fiber, 1,5 g tapioca, 1 g of PVA, 3 g chitosan, 10 mL of VCO. The characteristics of this bleaching tissue are bound cellulose, flexible textured paper, smooth texture, stronger when exposed to water, can absorb ethanol. This biodegradables wet wipes pH test obtained 2 results, namely with pH paper and Ph meters of 7 and 7,29, respectively. Biodegradable wet wipes irritation test conducted on 4 volunteers showed no signs of irritation. Keywords:Palm Fiber, Wet Wipes,  Biodegradable, Antibacterical, Palm leaves, Ethanol.